ANALYSIS OF KOMPAS NEWPAPER’S PERSPECTIVE ON INDONESIAN POLITICAL DYNAMICS IN 1998 : Analisis Perspektif Surat Kabar Kompas terhadap Dinamika Politik Indonesia Pada Tahun 1998 - Angelica Jolie Melvin; Aulia Fitriany; M. Khusni Mubarok (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
The purpose of this research is to see how Kompas Newspaper viewed Indonesia’s political devolepment in 1998, especially in the context of transition after the fall of New Order regime. This research focuses on three main aspects: 1) Results the research shows that Kompas Newspaper was first established on June 28 1965 by P.K. Ojong and Jakob Oetama. Kompas was created because the Indonesian Catholic Community needed an independent and reliable communication medium. It has journalism principle that must be cautious, neutral, and focused on the public interest. 2) After the New Order regime collapsed in May 1998, Indonesia entered a period of political transition towards open democracy. Kompas functioned as a strategic media that bridged the public interest with the dynamics that occurred among the political elite.  In 1999, Kompas discussed many important issues such as democratic elections after the New Order and the strengthening of democratic institutions such as the DPR and the Supreme Court through news, editorials, and opinion sections. 3) Kompas' perspective on political change since 1998 can be categorized as constructive, although critical.  This media shows the decline of the New Order as an important momentum to rebuild a fair and democratic political order. Kompas actively criticized various government policies, including addressing corruption, human rights violations, and political instability. This study uses a descriptive qualitative method with the approach of content analysis of news archives, editorials, and opinions published in Kompas newspaper during 1998-1999. The study shows that Kompas has a strong history as a media that maintains independence and prudence in handling political issues. During the New Order era, Kompas was an important media that carried out transformation, enabling discussions on democratization, information disclosure, and reformation.